Investigating the Behavioral Adaptation Model of Tourism Business Owners in Kermanshah Province facing COVID-19 Outbreak - Ehsan Khosravi; Nader Naderi; Bijan Rezaei; Hossein Azadi (جغرافیا و پایداری محیط)
It is obvious that the Covid-19 virus outbreak crisis has had many negative effects on tourism businesses worldwide; Therefore, it is necessary to study the adaptation behaviors to this crisis in order to reduce its adverse effects leading to manage the adaptive behaviors of this crisis by sharing experiences and to ensure the continuity of tourism businesses in times of crisis. The current study aims to investigate the behavioral adaptation model of tourism business owners in Kermanshah Province facing COVID-19 crisis. The population of this study includes business owners in the field of tourism in Kermanshah Province. Purposeful snowball sampling was used to select the interviewees. Sampling was continued until theoretical saturation was reached. In this study, theoretical saturation was obtained by examining 38 samples from the mentioned population. Data collection was done through open (unstructured) questionnaires, in-depth individual interviews, note-taking, document review, or often a combination of these methods. The results obtained from the research data in the open, axial and selective coding process were extracted and classified in the form of concepts. Based on the data; a "model of behavioral adaptation of tourism business owners in the face of the Covid-19 crisis" was designed and presented. In general, the results showed that the behaviors included two categories of reactive adaptive behaviors and planned adaptive behaviors that reactive adaptive behaviors are the basis for the destruction of businesses in the long run and planned adaptive behaviors paves the way for the growth and development of businesses in the long run. It is suggested that policymakers try to reduce reactive behaviors and improve planned behaviors in order to grow and develop businesses in the long run by adopting correct and principled policies.